If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -1(8 + 2x) = 9x + 5p 6p + (8 * -1 + 2x * -1) = 9x + 5p 6p + (-8 + -2x) = 9x + 5p Reorder the terms: -8 + 6p + -2x = 9x + 5p Reorder the terms: -8 + 6p + -2x = 5p + 9x Solving -8 + 6p + -2x = 5p + 9x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -8 + 6p + -5p + -2x = 5p + -5p + 9x Combine like terms: 6p + -5p = 1p -8 + 1p + -2x = 5p + -5p + 9x Combine like terms: 5p + -5p = 0 -8 + 1p + -2x = 0 + 9x -8 + 1p + -2x = 9x Add '8' to each side of the equation. -8 + 1p + 8 + -2x = 8 + 9x Reorder the terms: -8 + 8 + 1p + -2x = 8 + 9x Combine like terms: -8 + 8 = 0 0 + 1p + -2x = 8 + 9x 1p + -2x = 8 + 9x Add '2x' to each side of the equation. 1p + -2x + 2x = 8 + 9x + 2x Combine like terms: -2x + 2x = 0 1p + 0 = 8 + 9x + 2x 1p = 8 + 9x + 2x Combine like terms: 9x + 2x = 11x 1p = 8 + 11x Divide each side by '1'. p = 8 + 11x Simplifying p = 8 + 11x
| 7+9x=9x+7 | | 5(x+3)+9=(x-2)+6 | | 74x*8x*9x=1(0+2*68*7) | | 5a+18bc+15b+6ac= | | Y=-5x^2+500x | | -6x+4x+19-9x= | | m^(3/2)/m^(1/2) | | 4(x-3)-5x=13 | | -3(w+3)=-9w-21 | | 8x+13y+17z=58 | | 40-5y+8y-y^2= | | -10+4.5=-30 | | 74x-6=19+18x | | 6(5x+6)=306 | | 3[3-(-3)]= | | 8x+7-10x=10+3x+12 | | 8k-k-8= | | 1/3=13/x | | y=25(2x) | | y^2-9y+7y-63= | | 2x+5-7x=7-1(5x+2) | | 0.4x-0.5=0.3x+7 | | ln(x+6)-ln(3)=ln(16) | | (3t+4)t=0 | | -8x-6-x-3= | | y=4x^2-3x-10 | | y^2-5y-6y+30= | | 12=5-x-6x | | x^2-6x+2x-3=9x+27 | | Y=-2(X^4+2X^2)+8 | | 0.66666a+1=11 | | (k+3)+(k+k-11)+k=64 |